Management of urological injuries following gynecologic and obstetric surgery: A retrospective multicenter study - Keles, Ahmet; Hamid-zada, Ilkin; Arikan, Ozgur; Dalgic, Gurkan; Durmaz, Ali Selim; Keles, Esra; Yildirim, Asif (Kare Publ, 2024)
OBJECTIVE: Urinary system injuries may occur iatrogenically during some surgical procedures especially gynecological and obstetrical surgeries. Unfortunately, these injuries can lead to serious complications in patients. In this multicentric study, we aimed to review and report our experiences and results of urinary tract injuries identified during gynecological and obstetrical surgery. METHODS: We included women with urinary tract injuries during gynecological and obstetrical surgeries between January 2018 and October 2023 at four centers. Detailed data collected include patient demographics, surgical details, injury characteristics, diagnostic and treatment methods, timing of injury diagnosis and management reports of the patients. The incidence of bladder and ureter injuries was evaluated and the rate of intraoperative urological consultations was recorded. RESULTS: In a total of 328 patients with a median age of 47 years (24-90), urinary tract injuries were diagnosed, including 227 (69.2%) iatrogenic bladder injuries (IBI) and 101 (30.8%) iatrogenic ureteral injuries (IUI). These injuries were diagnosed in 299 patients (91.2%) during surgery and in 29 patients (8.8%) after the surgical procedure. We observed intraoperative detection rates of 71.9% for IBI and 28.1% for IUI. IBI (71.9%) was diagnosed significantly more frequently than IUI (28.1%) (p=0.001). Cesarean section resulted in significantly more frequent IBI, whereas tumor debulking surgeries resulted in more IUI (n=52, 56.5%) than the other types of procedures (p<0.001). CONCLUSION: Our study provides a comprehensive overview of iatrogenic urological injuries during gynecological and obstetrical surgeries. Although the bladder is the most frequently injured organ during gynecological and obstetric surgeries, early diagnosis and urological intervention are mandatory to prevent delayed complications. Surgeons must have a thorough understanding of the pelvic anatomy and appropriate surgical techniques to prevent iatrogenic injuries during surgery and ensure timely diagnosis and treatment of urinary tract injuries.
Keywords: Iatrogenic injury; gynecological and obstetrical surgeries; urinary system